International journal of ICT research and development in Africa - IGI eBooks; IGI Global; Information Resources Management Association (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA), 2010)
The International Journal of ICT Research and Development in Africa (IJICTRDA) publishes original, cutting-edge research articles on the use of information communication technologies in agriculture and rural development. Emphasizing new innovations and best practices in the use of ICT, diffusion and adoption methods, techniques, e-value creation, and policy issues, IJICTRDA focuses on information communication applications in agricultural and socio-economic development and poverty alleviation.
"An official publication of the Information Resources Management Association".
Also available in print.
Mode of access: World Wide Web.
Description based on: Vol. 1, issue 1 (Jan.-Mar. 2010); title from title screen (IGI Global, viewed Oct. 1, 2010).
Latest issue consulted: Vol. 1, issue 2 (Apr.-June 2010).
Keywords: Rural development -- Data processing -- Africa -- Periodicals; Agriculture -- Data processing -- Africa -- Periodicals; Information technology -- Africa -- Periodicals; Telecommunication -- Africa -- Periodicals; ICT applications in agricultural; E-customer relationship management; Food and agricultural marketing and market development; Supply chain governance; Integration of agricultural value chain; Agribusiness input supply and e-procurement strategies; Social capital development in agriculture; Rural mobile banking services; Rural environmental management; Agricultural information management and diffusion; Agro-based small and medium scale enterprises; Development issues for rural women; Farmer health service delivery; Farm productivity; Rural financial service delivery; Farm business management; Agritourism and regional economic integration; Rural digital divide; Agriculture development; Agro-portals and rural e-kiosks; Agricultural e-risk management policy; Farmer e-health policy; Food security policy; Poverty alleviation policy; Sustainable rural development policy; Electronic books